Examining Social Media Framing of Artificial Intelligence, AI Governance Structure, and Public Perception - Habeeb Daranijo; Isiaka Zubair Aliagan; Kamal Idowu Dauda; Raliat Ibrahim (Research and Development Agency Ministry of Home Affairs, 2024)
Effective governance frameworks are becoming increasingly important as Artificial Intelligence (AI) pervades all strata of society. This study examines the importance of social media in influencing public discourse and perception of issues related to AI governance. Specifically, the study examines social media coverage of Artificial Intelligence and AI governance structures. It also examines how the social media representation of AI may impact public understanding and inform policy decisions. Ultimately, it examines the potential of social media as a tool for promoting informed public debate and contributing to the development of responsible AI governance. The study adopts a multi-method approach, combining sentiment analysis and content analysis. The unit of analysis for the study comprises posts on social media platforms and stories from major online news sources over six years (2019–2024). The study adopts the machine learning analytic tool, Mentionlytics, to generate its data. The methodology combines both human and Mentionlytics categorization of themes, including societal implications, technical breakthroughs, and ethical considerations. Sentiment analysis is also used to monitor shifts in public perception and social media coverage over time of AI governance issues. The findings of the study add to the ongoing conversation about maximizing the benefits of AI while minimizing its potential concerns.